2007
DOI: 10.1177/095632020701800304
|View full text |Cite
|
Sign up to set email alerts
|

In VitroPre- and Post-Exposure Prophylaxis Using HIV Inhibitors as Microbicides Against Cell-Free or Cell-Associated HIV-1 Infection

Abstract: Several classes of microbicides are being evaluated for the prevention of sexual HIV transmission.In vivo, the infectious dose and viral source involved in transmission remain uncertain and it is likely that women will use microbicides both before and after high-risk HIV exposure. Therefore, we evaluated HIV entry inhibitors (EIs) and reverse transcriptase inhibitors (RTIs) for their ability to block cell-free and cell-associated HIV-1 infection in co-cultures of monocyte-derived dendritic cells (MO-DC) and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 45 publications
6
21
0
Order By: Relevance
“…Since then researchers from various fields have actively been developing technologies to combat the rapid spread of HIV. These strategies include pre-exposure prophylactics (28,41) and microbicides (14,31) designed to topically deliver single or combination antiviral agents. Currently, microbicide delivery systems under development include gels, rings, films, and suppositories.…”
mentioning
confidence: 99%
“…Since then researchers from various fields have actively been developing technologies to combat the rapid spread of HIV. These strategies include pre-exposure prophylactics (28,41) and microbicides (14,31) designed to topically deliver single or combination antiviral agents. Currently, microbicide delivery systems under development include gels, rings, films, and suppositories.…”
mentioning
confidence: 99%
“…As expected, no firefly luciferase activity was measured in the CCR5-negative X4M reporter cell line. Clearly, all antiretrovirals not only block viral spread to the target cells, but also inhibit viral spread The TCID 50 of BaL-infected effector cells (i.e., resting PBMC/CD4 ϩ T cells, activated PBMC/CD4 ϩ T cells, and macrophages) was determined in a 7-day coculture with R5M target cells. Firefly luciferase was used to assess target cell infection, and the TCID 50 was calculated using the method of Reed and Muench, expressed as the number of cells needed for 50% infection and plotted on the left y axis (black symbols).…”
Section: Resultsmentioning
confidence: 99%
“…TCID 50 determination of cell-free HIV and HIV-infected effector cells. The 50% tissue culture infective dose (TCID 50 ) was determined for cell-free BaL, as well as for BaL-infected effector cells (i.e., resting PBMC, activated PBMC, and macrophages) using the R5M cell line as HIV target cells. The FL reporter enzyme is transcribed and expressed under the influence of Tat-long terminal repeat (LTR) interaction and is therefore restricted to infected R5M cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, emtricitabine recommended dose is 200 mg once a day (QD) [2]. Both in vitro [3] and in vivo [4] testing demonstrated that emtricitabine presents enough potential to be tested in the prevention of HIV-1, either alone or in combination [5].…”
Section: Introductionmentioning
confidence: 99%